Analysis of the Prognostic Value and Potential Molecular Mechanisms of TREM-1 Overexpression in Papillary Thyroid Cancer via Bioinformatics Methods - Xie, Zhenyu; Li, Xin; He, Yuzhen; Wu, Song; Wang, Shiyue; Sun, Jianjian; He, Yuchen; Lun, Yu; Xin, Shijie; Zhang, Jian (Frontiers in Endocrinology, 2021)
Background: Triggering receptor expressed on myeloid cells-1 (TREM-1) has been reported as a biomarker in many cancers. However, the biological function of TREM-1 in papillary thyroid carcinoma (PTC) remains unknown. Methods: We obtained TREM-1 expression data from The Cancer Genome Atlas (TCGA) database. Enrichment analysis of coexpressed genes and TREM-1 methylation analysis were performed via LinkedOmics. The correlations between TREM-1 and immune infiltrates were investigated via ESTIMATE, TIMER and TISIDB. We analyzed the association of TREM-1 expression with pan-cancer overall survival via Gene Expression Profiling Interactive Analysis (GEPIA). Results: TREM-1 has lower methylation levels and higher expression levels in PTC tissues compared to normal tissues. TREM-1 expression is significantly associated with poor prognosis, advanced T classification, advanced N classification, and an increased incidence of BRCA2 and BRAF mutation. Genes coexpressed with TREM-1 participate primarily in immune-related pathways. TREM-1 expression is positively correlated with immune infiltration, tumor progression and poor overall survival across cancers. Conclusions: TREM-1 is a good prognostic and diagnostic biomarker in PTC. TREM-1 may promote thyroid cancer progression through immune-related pathways. Methylation may act as an upstream regulator of TREM-1 expression and biological function. Additionally, TREM-1 has broad prognostic value in a pan-cancer cohort.